Development of a composite friction modifier with carbon nanotubes for applications at the wheel–rail interface. (3rd June 2020) - Vélez, Juan Camilo; Cornelio, Jesús Antonio Carlos; Sierra, Robinson Buitrago; Santa, Juan Felipe; Hoyos-Palacio, Lina Marcela; Nevshupa, Roman; Toro, Alejandro
Wear of wheels and rails is a major problem in railway transportation industry. Solid lubricants constitute a cost-efficient alternative to control wear and friction at the wheel–rail interface, especially when a fine-tuned balance between traction force and energy consumption is sought. In this work, composite friction modifiers (CFMs) composed of a vinyl ester matrix reinforced with molybdenum disulfide and carbon nanotubes were developed. The total solid additive content was less than a half in comparison with a commercial product available on the market, which was used as a reference. A benchmarking study of the CFM was carried out by means of tribological tests in a twin-disc machine at a contact pressure of 1.1 GPa and different slip values. The results indicated that the developed CFM reduce coefficient of traction by 10% compared to unlubricated conditions that is similar to the reference. However, the total mass loss of steel components due to wear under CFM lubrication was lower than in the reference test.